BISNIS PERBANKAN MENJADI PILIHAN PADA ERA 4.0 BAGI KAUM MILENIAL UNIVERSITAS MAJALENGKA - Kurnadi, Engkun (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
World competition in the financial industry is increasing with the existence of fintech. The purpose of this community service is to socialize the banking business as an option in the 4.0 era for millennials, especially students of the Faculty of Economics and Business, University of Majalengka. During his journey, he specifically invited banking practitioners to give seminars related to banking business in the 4.0 era (digitalization). The number of participants who attended reached 300 participants consisting of management and accounting students from the Faculty of Economics and Business, University of Majalengka. The result of this activity is that students become interested in going directly into the banking world after graduating from college to work as well as the digital banking business at this time, where students are encouraged to be able to compete in the financial industry, especially according to their basic education which incidentally is a Bachelor of Management and Bachelor of Accounting.